Formulation and Evaluation of Oral Sustained Release Suspensions Using Ethyl Cellulose Microcapsules Containing Propranolol Hydrochloride Using Ion Exchange Resinates - SURESH, N.; ASHOK KUMAR, B.S.; SHESHADRI SHEKAR, D.; RAMNATH, K.V.; GIRIRAJ KULKARNI, T.; SURESH, B. (Asian Journal of Chemistry, 2010)
Ethyl cellulose coated ion exchange resinates of propranolol hydrochloride were prepared using amberlite IR 120 by solvent evaporation method. Among 5 batches of microcapsules (drug resinate-ethyl cellouse in ratio 1:1, 1:1.5, 1:2, 1:2.5 & 1:3), prepared an ideal batch (drug resinate-ethyl cellouse ratio 1.0:2.5) was selected for the formulation of sustained release suspension. 8 Batches of suspension were prepared using methyl cellulose and carboxyl methyl cellulose as suspending agents in 4 different concentrations (0.5, 1, 1.5 and 2 %). These suspensions were evaluated for physical stability (by determination of sedimentation volume), redispersibility and in vitro release patterns. The results showed that suspensions prepared with carboxyl methyl cellouse had better physical stability than those prepared with methyl cellulose and suspensions prepared with 1.5 carboxyl methyl cellouse as suspending agent showed optimum release and was found to ideal sustained release formulation.